2013
DOI: 10.3233/jbr-130049
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of fruit traits and phytochemicals in a highbush blueberry seedling population

Abstract: BACKGROUND: The fruit quality traits and the phytochemical content of blueberries are of increasing importance to researchers in the field of food and health and important breeding objectives. OBJECTIVE: The aim of this study was to gain preliminary information on parent's performances and variation of the fruit traits and phytochemicals from a small breeding population. METHODS: The breeding population was from a 3 × 4 factorial mating design, 120 seedlings in total. The fruit traits evaluated were weight, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Quantitative genetic studies in blueberry have focused on three main challenges: (I) identify the elite genotypes to be used as parents in future crosses [19,[148][149][150][151]; (II) estimate genetic parameters such as heritability, phenotypic and genetic correlations, and predict the expected change in a trait in response to selection-the breeder's equation [19,148] and (III) estimate the genotype-by-environment (G×E) interaction [13,19,152,153]. Genetics studies in blueberry have been reported for distinct traits; however, to our knowledge, only Cellon et al (2018) [19] have investigated the firmness trait.…”
Section: Quantitative Genetics Of Firmness Trait In Shb Blueberry Brementioning
confidence: 99%
“…Quantitative genetic studies in blueberry have focused on three main challenges: (I) identify the elite genotypes to be used as parents in future crosses [19,[148][149][150][151]; (II) estimate genetic parameters such as heritability, phenotypic and genetic correlations, and predict the expected change in a trait in response to selection-the breeder's equation [19,148] and (III) estimate the genotype-by-environment (G×E) interaction [13,19,152,153]. Genetics studies in blueberry have been reported for distinct traits; however, to our knowledge, only Cellon et al (2018) [19] have investigated the firmness trait.…”
Section: Quantitative Genetics Of Firmness Trait In Shb Blueberry Brementioning
confidence: 99%
“…Blueberry is a perennial shrub belonging to the genus Vaccinium in the Ericaceae family. It is popular worldwide because of the high nutritional value of its fruit and its strong antioxidant capacity [1,2]. Blueberry is an acid-loving plant [3], and a suitable soil pH for its optimal growth is approximately 4.0-5.0 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Acylation of ANC, for example, can positively influence the stability in a food but can attenuate the absorbance post-ingestion (Charron et al, 2009). The overall accumulation and retention of ANC vary according to genotype, environment, stage of maturity, and post-harvest handling practices (Charles et al, 2012;Connor et al, 2002;Gustafson et al, 2012;Kalt et al, 2001;Prior et al, 1998;Reyes-Carmona et al, 2005;Scalzo et al, 2013).…”
mentioning
confidence: 99%